Problem Pluralisme Agama dalam Prespektif al-Qur’an (Kajian Muqaranah Q.S. al-Baqarah (2): 62, Q.S. al-Maidah (5): 69, Q.S. al-Haj (22): 17) - Diaz Supandi, Muhammad (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2026)
This study examines the theological problem of religious pluralism from the perspective of the Qur'an through a comparative (muqaranah) analysis of three key verses: Q.S. al-Baqarah (2): 62, Q.S. al-Maidah (5): 69, and Q.S. al-Haj (22): 17. The academic issue arises from the tension between inclusive messages that acknowledge the potential salvation for non-Muslims based on universal faith and righteous deeds, and exclusive verses that emphasize Islamic finality and divine authority. Using a qualitative library research method with a comparative interpretive approach, this study analyzes classical and contemporary commentaries to explore hermeneutical nuances, historical contexts, and possible relational interpretations (nasikh-mansukh or specificity-generality). The findings reveal that the Qur'an constructs a multi-layered theological paradigm: it recognizes transcendent criteria for salvation (faith and good deeds), affirms Islam's truth claim, and simultaneously asserts Allah's absolute authority as the final judge. This dialectic avoids both religious relativism and exclusivist dogmatism, offering a balanced framework for interfaith coexistence. The novelty lies in the systematic comparison of these verses, highlighting the Qur'an's internal dynamics and proposing a